Recent progress on operator theory and approximation in spaces of analytic functions - Conference on Completeness Problems, Carleson Measures, and Spaces of Analytic Functions (Djursholm, Sweden 29 June - 3 July 2015); Beneteau, Catherine; Condori, Alberto A.; Liaw, Constanze; Ross, William T.; Sola, Alan A. (Providence : American Mathematical Society, 2016)
This volume contains the Proceedings of the Conference on Completeness Problems, Carleson Measures, and Spaces of Analytic Functions, held from June 29-July 3, 2015, at the Institut Mittag-Leffler, Djursholm, Sweden. The conference brought together experienced researchers and promising young mathematicians from many countries to discuss recent progress made in function theory, model spaces, completeness problems, and Carleson measures. This volume contains articles covering cutting-edge research questions, as well as longer survey papers and a report on the problem session that contains a collection of attractive open problems in complex and harmonic analysis.
* K. Bickel and C. Liaw, Properties of vector-valued submodules on the bidisk* A. Bourhim and J. Mashreghi, Composition operators on the Hardy-Hilbert space $H^2$ and model spaces $K_\Theta$* I. Chalendar, E. Fricain, and D. Timotin, A survey of some recent results on truncated Toeplitz operators* M. Fleeman and D. Khavinson, Approximating $\overline{z}$ in the Bergman space* S. R. Garcia, J. Mashreghi, and W. T. Ross, Real complex functions* P. Gorkin and B. D. Wick, Thin interpolating sequences* A. Hartmann and M. Mitkovski, Kernels of Toeplitz operators* E. Saksman and K. Seip, Some open questions in analysis for Dirichlet series* D. Seco, Some problems on optimal approximants* C. Beneteau, A. A. Condori, C. Liaw, W. T. Ross, and A. A. Sola, Some open problems in complex and harmonic analysis: Report on problem session held during the conference Completeness problems, Carleson measures, and space of analytic functions.
Includes bibliographical references.
Keywords: Operator theory -- Congresses; Analytic spaces -- Congresses; Analytic functions -- Congresses